Efisiensi Energi Sistem Komunikasi Kooperatif Multi-relay Quantize and Forward Berdasarkan Pemilihan Relay - Fityanul Akhyar; Nasaruddin; Rusdha Muharar (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2017)
Currently, the increasing energy consumption is a global issue. Information technology and telecommunication industry is one of the areas with the largest energy consumption. The growth of mobile data users is an issue and the biggest challenge for the future. The cooperative wireless communication system has been the focus of research as one of the information delivery strategy with more efficient energy consumption. Energy efficiency in the cooperative wireless communication system can be improved by using a relay between base station and user device, where the distance between base station and user can be shortened, thus, the energy transmission can be minimized. Relay mechanism can be built by utilizing the protocol in the cooperative communication system, such as amplify and forward (AF), decode and forward (DF), and quantize and forward (QF). Relay-selection is an important issue in a cooperative wireless communication system that can reduce energy consumption at the system level. This study analyzes energy efficiency of multi-relay QF cooperative communication for line-of-sight (LOS) and non-line-of-sight (NLOS) environment based on relay selection strategies: reactive and proactive relay selection. A computer simulation is conducted based on a system model and mathematical analysis. Energy efficiency is calculated based on power consumption of signal transmission and observed in the distance between the source, relay, and destination. Simulation result shows that multi-relay QF networks with relay selection consume lower energy than without relay selection, hence, the energy usage in the relay selection networks is more efficient. Moreover, the strategy of proactive relay selection provides low energy consumption and high energy efficiency compared to the reactive relay selection strategy.